The Role of trophic niche in eel head shape dimorphism - Teesalu, Paul (Eesti Maaülikool, 2019)
Master’s Thesis Chair of Hydrobiology and Fishery The European eel is a critically endangered fish species with a complex life cycle. Many aspects of eel ecology are poorly investigated; therefore, it is crucial to have a thorough understanding of this fish species for better stock management practices and conservation actions. In this thesis we caught and measured the head width of eels from the Estonian lakes of Saadjärv and Võrtsjärv. We hypothesised that individuals with narrow heads would be primarily benthivorous, whereas broad-headed individuals were likely to be piscivorous. Lake ecosystems and the subsequent difference in food availability could play a role in the formation of either head morph. Thus, our second hypothesis is that Lake Saadjärv, with an average macroinvertebrate biomass of 2.5 g/m2 would have more broad-headed eels than Lake Võrtsjärv, which has a higher macroinvertebrate biomass of 6.6 g/m2 . We combined gut content analyses and stable isotopes of δ 15N and δ 13C to determine and compare trophic niches of eel populations. Gut content analyses results confirm that eels in Saadjärv are affected by head shape in their feeding habits, with narrow-headed eels consuming proportionally more macroinvertebrates and broad-headed eels consuming more fish. This was confirmed with stable isotope analyses- broad-headed eels were significantly more enriched in δ 15N and therefore had a higher trophic position than narrow-headed eels. In Lake Võrtsjärv nearly all eels (95%) displayed a narrow head shape, suggesting a diet based mainly on macroinvertebrates, particularly chironomids. In line with our expectations stable isotope analyses indicated that the eel population in Võrtsjärv rely mostly on Chironomus plumosus and marginally on other benthic macroinvertebrates. The occurance of broad-headed eels was indeed higher in Saadjärv (31%) than in Võrtsjärv (2.3%) indicating that food availability plays a crucial role in eel head morphology Euroopa angerjas on keerulise elutsükkliga kriitiliselt ...